2016
DOI: 10.1016/j.vaccine.2016.01.017
|View full text |Cite
|
Sign up to set email alerts
|

An initial examination of the potential role of T-cell immunity in protection against feline immunodeficiency virus (FIV) infection

Abstract: The importance of vaccine-induced T-cell immunity in conferring protection with prototype and commercial FIV vaccines is still unclear. Current studies performed adoptive transfer of T cells from prototype FIV-vaccinated cats to partial-to-complete feline leukocyte antigen (FLA)-matched cats a day before either homologous FIVPet or heterologous-subtype pathogenic FIVFC1 challenge. Adoptive-transfer (A–T) conferred a protection rate of 87% (13 of 15, p<0.001) against FIVPet using FLA-matched T cells, whereas al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The latter finding is noteworthy since prototype vaccine afforded 100% protection against FIV FC1 ( Table 1 , Study 4b). Since prototype vaccine-induced FIV-specific CTL and polyfunctional T-cell activities [ 61 , 62 ], the likelihood of vaccine-induced T-cell immunity playing a major role in protection against heterologous subtype viruses was a strong possibility.…”
Section: The Role Of Vaccine-induced Antibody (Ab) Immunity In Promentioning
confidence: 99%
See 3 more Smart Citations
“…The latter finding is noteworthy since prototype vaccine afforded 100% protection against FIV FC1 ( Table 1 , Study 4b). Since prototype vaccine-induced FIV-specific CTL and polyfunctional T-cell activities [ 61 , 62 ], the likelihood of vaccine-induced T-cell immunity playing a major role in protection against heterologous subtype viruses was a strong possibility.…”
Section: The Role Of Vaccine-induced Antibody (Ab) Immunity In Promentioning
confidence: 99%
“…Above studies, however, did not demonstrate whether the transferred vaccine-induced memory B cells were working in synergy with the transferred anti-FIV T cells. In recent studies, purified T and B cells from vaccinated AT donors were adoptively transferred to partial-to-compete MHC matched recipients ( Table 6 , Studies 4–7) [ 62 ]. In Study 4 that was based on MHC matching by mixed leukocyte reaction (MLR) ( Table 6 , Study 4), 3/4 (75%) AT recipients of MLR-matched immune T cells were protected, whereas none (0/4) of the recipients receiving either MLR-matched immune B cells or unrelated non-immune PBMC were protected.…”
Section: The Role Of Vaccine-induced T-cell Immunity In Prophylactmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that major histocompatibility complex class I (MHC-I) molecules are critical for activating cytotoxic T lymphocytes (CTLs) to control HIV infection (9)(10)(11)(12). CD8 ϩ T-cell proliferation responses control FIV infection, and MHC-I molecule expression on microglial cells is transiently upregulated at the onset of FIV reproduction (13)(14)(15)(16)(17). Elevated MHC expression can also be observed in HIV and simian immunodeficiency virus (SIV) (18,19).…”
mentioning
confidence: 99%